2020
DOI: 10.1002/edm2.218
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular complications in COVID‐19 patients with or without diabetes mellitus

Abstract: Introduction Coronavirus disease 2019 (COVID‐19) has become a major global crisis. Preliminary reports have, in general, indicated worse outcomes in diabetes mellitus (DM) patients, but the magnitude of cardiovascular (CV) complications in this subgroup has not been elucidated. Methods We included 142 patients admitted with laboratory‐confirmed COVID‐19 from April 1st to May 30th 2020; 71 (50%) had DM. We compared baseline demographics and study outcomes between those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 8 publications
0
25
0
1
Order By: Relevance
“…Of the 783 studies identified from the literature search (216 on Pubmed and 567 on EMBASE), 31 studies were selected according to the inclusion and exclusion criteria and included in the analysis [ 3 , 10 , 11 , 12 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] ( Figure S1 in Supplementary Materials ), with a total of 187,716 COVID-19 patients. Baseline characteristics of the studies included are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 783 studies identified from the literature search (216 on Pubmed and 567 on EMBASE), 31 studies were selected according to the inclusion and exclusion criteria and included in the analysis [ 3 , 10 , 11 , 12 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] ( Figure S1 in Supplementary Materials ), with a total of 187,716 COVID-19 patients. Baseline characteristics of the studies included are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were held in Europe [ 10 , 11 , 25 , 29 , 31 , 33 , 37 , 39 , 42 , 43 , 44 , 47 , 50 ], nine in North America [ 3 , 28 , 30 , 32 , 41 , 45 , 46 , 49 , 51 ], four in Asia [ 26 , 34 , 35 , 48 ], and five in other geographical locations, including one multinational study [ 12 , 27 , 36 , 38 , 40 ]. Twenty-five studies were observational retrospective [ 3 , 10 , 12 , 26 , 28 , 30 , 31 , 32 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], four were based on prospective observational analysis of single center cohorts [ 11 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the chaotic initial months of the pandemic, an increasing number of studies have shown that the severity of SARS-CoV-2 is directly related to the health status of the infected individuals[ 2 ] and also with gender[ 3 ]. Severe complications and an increased risk of mortality have been linked with various pathologies[ 2 , 4 ] including obesity, diabetes, lung disease, and hypertension[ 2 , 4 - 7 ]. SARS-CoV-2 invades the mucosal cells of the host, mainly through the nose and mouth.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients with established cardiovascular disease have an increased risk for severity and mortality with SARS-CoV-2 infection, mainly due to ACE2 receptors abundance in the cardiovascular system, which represents the gateway for the virus entry in the heart [ 7 ]. Although still debated, acute SARS-CoV-2 induced myocarditis represents one of the most common cardiovascular SARS-CoV-2 complicacy along with other pathogens with cardiac tropism [ 8 , 9 ]. Therefore, acute myocarditis presents across a variable range of clinical severity and is a significant diagnostic challenge in the SARS-CoV-2 infection era, considering that diffuse myocardial injury was also detected in the early convalescent stage of SARS-CoV-2 infected and recovered patients who had no active cardiac symptoms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%